1981
DOI: 10.1007/bf02032495
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-fixing bacteria associated with bark beetles

Abstract: Nitrogen-fixingEnterobacter agglomerans andEnterobacter spp. were consistently isolated from the bark beetleDendroctonus terebrans. Large populations of nitrogen-fixing bacteria were found with the beetle, although no in situ acetylene reduction was demonstrated. The constant occurrence of nitrogenfixing bacteria withD. terebrans suggests a symbiotic relationship. Nitrogen-fixing bacteria were also isolated from the bark beetlesDendroctonus frontalis andIps avulsus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(58 citation statements)
references
References 25 publications
0
55
0
3
Order By: Relevance
“…Diazotrophic enrichment cultures were obtained by adding subsamples of 0.5 g soil to 125 ml serum-flasks containing 100 ml N-free semisolid medium [27]. The medium contained (g·l −1 ): 0.1, MgSO 4 ·7H 2 O; 0.5, sodium thioglycolate; 0.008, ferric citrate; 0.008, Na 2 MoO 4 ·2H 2 O, and agar 0.1% (w/v).…”
Section: Culture Enrichments and Isolation Of Free Living Nitrogen-fimentioning
confidence: 99%
“…Diazotrophic enrichment cultures were obtained by adding subsamples of 0.5 g soil to 125 ml serum-flasks containing 100 ml N-free semisolid medium [27]. The medium contained (g·l −1 ): 0.1, MgSO 4 ·7H 2 O; 0.5, sodium thioglycolate; 0.008, ferric citrate; 0.008, Na 2 MoO 4 ·2H 2 O, and agar 0.1% (w/v).…”
Section: Culture Enrichments and Isolation Of Free Living Nitrogen-fimentioning
confidence: 99%
“…Breznak (1975) suggested that N 2 -fixation rates may be higher in young, growing larvae due to higher N demands and this may also be the case for other wood-feeding insects. Consistent with this view, nearly half the bark beetle (Ips avulsus Eichhoff) larvae tested by Bridges (1981) exhibited acetylene reduction activity, whereas none of the adults was found to possess this ability. However, elevated rates of acetylene reduction in younger developmental stages have not been shown in all studies on wood-feeding insects (Rohrmann & Rossman, 1980;Curtis & Waller, 1998).…”
Section: Gut-dwelling Microbesmentioning
confidence: 62%
“…A number of early efforts attempted to identify the organisms responsible for N 2 fixation in the guts of wood-feeding insects by culturing them on N-free media and testing for acetylene reduction (French et al, 1976;Potrikus & Breznak, 1977;Eutick et al, 1978;Bridges, 1981;Kuhnigk et al, 1996). Because only a small proportion of gut microbes can be cultured, however, this approach provides limited information.…”
Section: Gut-dwelling Microbesmentioning
confidence: 99%
“…4 Furthermore, the galleries constructed by bark beetles become habitat for a myriad of species. 11 Vast numbers of fungi 30 , bacteria 3 , mites 10,21 , and nematodes 16,19 along with other predatory and parasitic arthropods 22,24 inhabit the phloem material. The techniques provided here allow for direct observation of bark beetles, mites, and wood borers that typically live in subcortical environments.…”
Section: Introductionmentioning
confidence: 99%